The effect of novelty on travel intention: the mediating effect of brand equity and travel motivation. Issue 6 (4th September 2020) - Zhang, Yucheng; Li, Jing; Liu, Chih-Hsing; Shen, Yimo; Li, Guiquan
Abstract : Purpose: Research on the relationship between novelty and travel intention is lacking. This study attempts to fill this gap by developing a theoretical model to explain how novelty influences travel intention through two mediating paths: brand equity and tourist motivation. Design/methodology/approach: In this study, data were collected from 466 foreign visitors to Taiwanese night markets. To test the model, the authors applied structural equation modeling (SEM) to identify the critical attributes that predicted foreign tourists' travel intentions. Findings: The SEM analysis indicated that novelty in tourism management was related to brand equity and intrinsic motivation, which increased foreign tourists' travel intentions and offered advantages for highly competitive, high-density night markets in Taiwan. In addition, brand equity was an important mediator that connected novelty and tourists' travel intentions. Finally, novelty indirectly affected travel intention and intrinsic motivation through brand equity. Research limitations/implications: There may exist potential moderators in the relationships among the brand equity and travel intention categories. Future research studies could explore whether any moderators influence the relationship mechanisms examined in this study. Originality/value: This research expands on previous research studies that have focused on the value of travel intention. Furthermore, the study uses brand equity theory (BET) and the theory of planned behavior (TPB) to examine the mediating effect of intrinsic motivation on the relationship between novelty and travel intention.